Toll-like receptor 2 (−196 to −174) del and TLR1 743 A > G gene polymorphism—a possible association with drug-resistant tuberculosis in the north Indian population - Varshney, Deepika; Singh, Shoor Vir; Mohanty, Keshar Kunja; Kumar, Santosh; Varshney, Nitin; Sinha, Ekata; Barik, Sushanta Kumar (Frontiers in Microbiology, 2024)
Objectives: To analyze the association of TLR2 deletion (-196 to -174) and TLR1 743 A>G gene polymorphism with drug resistance tuberculosis (PTB, MDR-TB and XDR-TB) in a population from Agra Uttar Pradesh. Methods: The present case-control study included 101 pulmonary TB patients, 104 multidrug-resistant TB patients, 48 extremely drug-resistant TB patients and 130 healthy and unrelated controls residing in the same locality as that of the cases. The genotyping method for TLR2 deletion (-196 to -174) was carried out by allele-specific polymerase chain reaction (PCR) and TLR1 743 A>G gene polymorphism was performed by hybridization probe chemistry in Roche Real-Time PCR. Genotype and allele frequencies were analyzed by chi-square test. Cytokine levels were measured by ELISA and compared using Mann Whitney and Kruskal-Wallis test. Results: The frequency of heterozygous (Ins/del) genotypes for TLR2 (-196 to -179) polymorphism was predominant in XDR-TB patients (0.56) whereas heterozygous A/G genotypes were predominant in healthy controls (0.56) for TLR1 743A>G gene polymorphism. The heterozygous genotype of TLR2 deletion polymorphism was found to be significantly higher in XDR-TB (P=0.0001). TLR1 743 A>G SNP, AG genotypes were found to be significantly associated with healthy controls than PTB (P=0.047). The level of serum cytokines (IL-6, TNF-α and IFN-γ) was also found to be significantly different among TB patients and healthy controls. Conclusions: The findings suggested that in the present population, the heterozygous (Ins/Del) genotype and deletion allele of TLR2 deletion (-196 to -174) polymorphism is associated with the risk for the development of drug-resistant TB. Further, TLR1 743 A>G gene polymorphism, A/G genotype and G allele are found associated with healthy controls suggesting the protective role against TB.